Sobre anomalías e interpretación de los objetos orientalizantes en la Meseta - Moreno Arrastio, Francisco José (Gerión. Revista de Historia Antigua, 2001)
This notes are intending to take one step further in the study of the Ideas which has been used in order to interpret orientalizing Artifacts found in the Middle Tajo Valley. This has been done by using homeric verses and a different perspective of the relations between Phoenician colonies and natives, in which the Ramdom Processes created by conflicts are of dialectical nature.